Distinct phenotype of hepatotoxicity associated with illicit use of anabolic androgenic steroids. Issue 1 (13th November 2014) - Robles‐Diaz, M.; Gonzalez‐Jimenez, A.; Medina‐Caliz, I.; Stephens, C.; García‐Cortes, M.; García‐Muñoz, B.; Ortega‐Alonso, A.; Blanco‐Reina, E.; Gonzalez‐Grande, R.; Jimenez‐Perez, M.; Rendón, P.; Navarro, J. M.; et al.
Summary Background We have observed an increase in hepatotoxicity (DILI) reporting related to the use of anabolic androgenic steroids (AAS) for bodybuilding. Aim To characterise phenotype presentation, outcome and severity of AAS DILI. Methods Data on 25 cases of AAS DILI reported to the Spanish (20) and Latin‐American (5) DILI Registries were collated and compared with previously published cases. Results AAS DILI increased from representing less than 1% of the total cases in the Spanish DILI Registry in the period 2001–2009 to 8% in 2010–2013. Young men (mean age 32 years), requiring hospitalisation, hepatocellular injury and jaundice were predominating features among the AAS cases. AAS DILI caused significantly higher bilirubin values independent of type of damage when compared to other drug classes (P = 0.001). Furthermore, the cholestatic AAS cases presented significantly higher mean peak bilirubin (P = 0.029) and serum creatinine values (P = 0.0002), compared to the hepatocellular cases. In a logistic regression model, the interaction between peak bilirubin values and cholestatic damage was associated with the development of AAS‐induced acute kidney impairment (AKI) [OR 1.26 (95% CI: 1.035–1.526); P = 0.021], with 21.5 ×ULN being the best bilirubin cut‐off point for predicting AKI risk (AUCROC 0.92). No fatalities occurred. Conclusions Illicit recreational AAS use is a growing cause of reported DILI that can lead to severe hepatic and renal injury. AAS DILI is associated with a distinct phenotype, characterised by considerable bilirubin elevations independent of type of damage. Although hepatocellular injury predominates, acute kidney injury develops in cholestatic cases with pronounced jaundice.